Clinical characteristics of antithyroid drug-induced aplastic anemia cases over the past 30 years - Cheng, Ying; Xia, Xin-Yu; Zhang, Wei; Ren, Li; Tian, Chen-Fu; Liu, Dan; Xue, Gang (Frontiers in Endocrinology, 2023)
Objective: Investigate the clinical characteristics of cases with antithyroid drugs induced aplastic anemia over past 30 years. Methods: The data of patients with antithyroid drugs induced aplastic anemia was reviewed in PubMed and Wanfang Medical Network databases from 1992 to August 2022. The clinical characteristics, such as age distribution, gender tendency, common symptoms, blood cells count and bone marrow features, treatment strategy and prognosis, were analyzed. Results: 17 cases (male: female=1:16) had been retrieved. Patients' age ranged from 16 to 74 years (median 50 years). 82.3% (14/17) of patients were administered methimazole (MMI), and 78.6% of them had MMI≥30 mg/day. 88.2% (15/17) patients had sore throat and fever, and 47.1% (8/17) patients had hemorrhagic symptoms. Aplastic anemia occurred within 6 months after initiation antithyroid therapy in 94.1% of patients. Agranulocytosis (94.1%) was the most common and earliest blood cell change, and 47.1% of patients experienced progressive platelet decline in the process of treatment. The treatments include timely withdrawal of antithyroid drugs, broad-spectrum antibiotics, granulocyte colony-stimulating factor (G-CSF)/granulocyte-macrophage colony-stimulating factor (GM-CSF), glucocorticoids and other immunosuppressive agents, and supportive treatments such as erythrocyte transfusion and platelet transfusion. 70.6% of patients had complete or near-complete remission within 8 days to 6 weeks. Conclusion: Aplastic anemia is a rare and serious adverse reaction of antithyroid drugs, which is more common to women. It usually occurs during early treatment with high-dose antithyroid drugs. Most patients have a good prognosis after timely drug ceasing and appropriate treatment.